Socioeconomic Differences in Health over the Life Cycle in an Egalitarian Country - Hans van Kippersluis; Owen O'Donnell; Eddy van Doorslaer; Tom Van Ourti (Tinbergen Institute, 2009)
A strong relationship between health and socioeconomic status is firmly established. Yet, partly due to the multidimensional and dynamic nature of the variables, the causal mechanisms connecting them are poorly understood. This paper argues that adoption of a life-cycle perspective is essential to uncover these causal pathways. A life-cycle perspective also allows investigation of whether the socioeconomically disadvantaged, on top of a lower health level, experience a sharper deterioration of their health over the life cycle. We show that in the Netherlands, as in the US, the socioeconomic gradient in health widens until late-middle age and narrows thereafter. The analysis and the available evidence suggests that the widening gradient is attributable both to health-related withdrawal from the labor force, resulting in lower incomes, and the cumulative protective effect of education on health outcomes. The less educated suffer a double health penalty in that they begin adult life with a slightly lower health level, which subsequently declines at a faster rate. The observed narrowing of the gradient in old age is partly an artefact stemming from the fact that only the most healthy of the disadvantaged survive into old age. It also reflects that after middle age, withdrawal from the labor force increasingly occurs for non health-related reasons.
Keywords: D30; D31; I10; I12; 330; Health; Socioeconomic Status; Life Cycle; Soziale Lage; Gesundheit; Lebensverlauf; Soziale Ungleichheit; Gesellschaftsordnung; Niederlande; USA